ENHANCING PKK'S SKILLS IN SUKA MAKMUR VILLAGE FOR ORGANIC WASTE MANAGEMENT USING THE COMPOSTING BAG METHOD - Tumanggor, Winni R.E.; Chahaya, Indra; Nursa’adah, Nursa’adah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Household waste is Indonesia's largest waste source, while food waste is the most significant composition. Waste remains unresolved in Suka Makmur Village due to poor management practices such as burning waste, littering, and a lack of public awareness, which can negatively impact community health and the environment. Compost fertilizer production using composting bags is one of the strategies that can be implemented to manage organic waste. This service aims to enhance the knowledge and skills of the PKK (Family Empowerment and Welfare) regarding composting using composting bags made from the kitchen and organic waste to create a clean kitchen. The methods used in this service include presenting material related to clean kitchen training, practical composting exercises, assessing participants' knowledge through pre-tests and post-tests, question-and-answer discussions, and monitoring and evaluating the processing of organic and inorganic waste. The post-test results on the knowledge and skills from applying composting bags showed an increase of 115.38%. Based on the monitoring and evaluation results, it was found that the participants displayed high enthusiasm for managing kitchen waste and were able to manage organic waste.